GE_GERICHTE P/9801/2004 vom 7. Juni 2007 - GE Cour de justice (2007)
; FAUX INTELLECTUEL DANS LES TITRES ; FAUX MATÉRIEL DANS LES TITRES ; FIXATION DE LA PEINE | CP.2.2; CP.110.4; CP.251.1; CP.47; CP.50; CP.40